2015
DOI: 10.1007/s00339-015-9324-8
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study on the vibration of carbon and boron nitride double-walled hybrid nanotubes

Abstract: Synthesis of hybrid nanotubes to overcome the drawbacks of individual pure nanotubes in order to apply them in novel nanodevices has attracted great interest of researchers. To this end, pure single-and double-walled boron nitride nanotubes together with carbon and boron nitride double-walled hybrid nanotubes are simulated through molecular dynamics simulations in order to study their vibrational behavior. The natural frequency of nanotubes is computed, and the effects of geometrical parameters and boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…1b). It is noted that such a non-planar whirling motion of hybrid nanotubes is in contrast to the conventional transverse vibration reported for CNTs and BNNTs [14][15][16], where the oscillation trajectory of the cross-section is a straight line. To further study the non-planar whirling motion observed for BN-CNTs we plotted the kinetic energy time history in Fig.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…1b). It is noted that such a non-planar whirling motion of hybrid nanotubes is in contrast to the conventional transverse vibration reported for CNTs and BNNTs [14][15][16], where the oscillation trajectory of the cross-section is a straight line. To further study the non-planar whirling motion observed for BN-CNTs we plotted the kinetic energy time history in Fig.…”
mentioning
confidence: 68%
“…Obviously, homogenous nanotubes, e.g., CNTs or BNNTs, only vibrate in one transverse direction due to their axisymmetric cross-sections [14][15][16]. Thus, newly fabricated hybrid nanotubes are expected to provide a solution to the long-standing issue in achieving the nanosensors for measuring atomic-scale mass.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In literature search, studies about viscoelastic CNT modeling can be found but in majority of papers an elastic structure assumption have been considered. Ansari and Ajori [10] carried out the MD simulation of double-walled Carbon and Boron-Nitride hybrid nanotubes. Static and dynamic analysis of nanorods [11], microbeams [12] and functionally graded Rayleigh beams [13] were investigated by researchers.…”
Section: Introductionmentioning
confidence: 99%